Goal as a Form of Representing the Conceptual Approaches to the Process of Teaching Native Language to Primary School Pupils in the Mountain Areas - Kotyk, Tetiana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The essence of the goal of language teaching, historical legacy of Pedagogy in the field of establishing the content of primary education and conceptual grounds for defining the goal and content of language teaching for primary school pupils with the emphasis on the Carpathians location have been developed.